2013
DOI: 10.1007/s00270-013-0766-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Radiation Safety Glasses in Interventional Radiology

Abstract: The efficacy of radiation protection glasses depends on the orientation of the operator's head relative to the irradiated volume. Glasses can offer good protection to the eye under clinically relevant conditions. However, the performance in clinical practice in our study was lower than expected. This is likely related to nonoptimized room geometry and training of the staff as well as measurement methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 20 publications
8
66
0
2
Order By: Relevance
“…This is reflected by the recent recommendation of the International Commission on Radiological Protection to reduce the equivalent dose limit for eye lenses from 150 to 20 mSv/ year [15]. As distances from irradiated patient's body part to the staff member's breast and eye lenses are comparable, the measured over-lead doses can be taken as approximation of the staff member's procedural eye lens dose [16]. The ICRP stated that the eye lens dose can be sufficiently assessed using the operational quantity Hp(0.07) [17], which can be estimated from the Hp(10) by means of conversion factors published by the ICRP [18].…”
Section: Discussionmentioning
confidence: 98%
“…This is reflected by the recent recommendation of the International Commission on Radiological Protection to reduce the equivalent dose limit for eye lenses from 150 to 20 mSv/ year [15]. As distances from irradiated patient's body part to the staff member's breast and eye lenses are comparable, the measured over-lead doses can be taken as approximation of the staff member's procedural eye lens dose [16]. The ICRP stated that the eye lens dose can be sufficiently assessed using the operational quantity Hp(0.07) [17], which can be estimated from the Hp(10) by means of conversion factors published by the ICRP [18].…”
Section: Discussionmentioning
confidence: 98%
“…Challa found that eyeglasses reduced lens dose in cardiology procedures to the left and right eye by 67 and 45 %, respectively [56], and a similar cardiology study found a left eye dose reduction of only 35 % [57]. Another study assessed eyeglass protection in a wide range of interventional procedures, finding a dose reduction factor of 2.1 for the left (tube-side) eye and no significant dose reduction for the right eye [52].…”
Section: Techniques For Minimizing Lens Exposurementioning
confidence: 90%
“…In general, shielding offers protection that is superior to that of leaded eyeglasses [50,52,61]. Shielding avoids the gaps in the protective barrier that plague leaded eyeglasses and provides excellent protection for both eyes.…”
Section: Techniques For Minimizing Lens Exposurementioning
confidence: 96%
See 2 more Smart Citations